Aspects juridiques de la crise américano-iranienne - Arbour, J.-Maurice (Les Cahiers de droit, 1980)
From the first day the American Embassy was invaded and its diplomatic staff was seized as hostages by Iran, the United States of America has pursued every legal channel in order to resolve this crisis by peaceful means. Its efforts started with the immediate dispatch of Mr. Ramsey Clark on a mission to negotiate with the government of Iran and were continued in the United Nations through the Secretary General, the Security Council, the U.N. Commission of Inquiry and the World Court. Though one can say that all disputes may theoretically be capable of settlement according to rules of law, it should also be said, as a matter of fact, that international law often has only limited relevance to disputes arising among States. This is so because international legal rules operate within a system which has no general scheme of sanctions and no central organ for the enforcement of international legal rights. States have traditionally utilized coercitive measures short of war in attempting to prevail in disputes with other States. Does this authorize a State to intervene by the use of force for the protection of its nationals abroad ? Even though, from the standpoint of morality, the abortive U.S. rescue operation in Iran may have had sound justifications, any legal justifications that could be put up had to give way before the principle of territorial sovereignty.